When it falls apart - Bybee, Catherine (The D'Angelos, 2022)
"Brooke Turner has always had a complicated relationship with her father. But when his health takes a turn for the worse, she drops everything to care for him. He's her dad, after all, and he needs her. What Brooke doesn't anticipate is the unraveling of her long-term relationship and a cross-country move to San Diego's Little Italy. Luca D'Angelo is the oldest of three children and a single father to a young daughter. When his mother rents the top floor of their house to Brooke, he's angry. Who is this beautiful stranger with no ties to the neighborhood? Can she be trusted in such close proximity to his family? As Luca learns of Brooke's difficult journey with her ailing father, his heart softens. And Brooke, who witnesses Luca's struggle as a single parent, develops feelings for him, too. But when it all falls apart, will love heal their wounded hearts?" -- Amazon.